1993
DOI: 10.1128/aac.37.3.457
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and nucleotide sequence of the Campylobacter jejuni gyrA gene and characterization of quinolone resistance mutations

Abstract: The gyrA gene of Campylobacterjejuni UA580, which encodes the A subunit of DNA gyrase, was cloned and its nucleotide sequence was determined. An open reading frame of 2,589 nucleotides was identified, which could code for a polypeptide of 863 amino acids with a Mr of 97 kDa. Both the nucleotide sequence and the putative amino acid sequence show ca. 50% identity with those of other gyrA genes from gram-positive and gram-negative bacteria. Similar mutations were also identified in ciprofloxacin-resistant isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
276
5

Year Published

1995
1995
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 259 publications
(313 citation statements)
references
References 36 publications
32
276
5
Order By: Relevance
“…This mutation is the most prevalent in clinical and veterinary isolates, among other described mutations (Thr86Ala, Thr86Lys, Ala87Pro, Asp90His, Asp90Tyr, etc.) (Wang et al, 1993;Bachoual et al, 2001;Piddock et al, 2003) mostly of in vitro origin (Bachoual et al, 2001). One isolate possessed another mutation in QRDR, Pro104Ser, previously described in isolates of animal and human origin (Piddock et al, 2003;Jesse et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This mutation is the most prevalent in clinical and veterinary isolates, among other described mutations (Thr86Ala, Thr86Lys, Ala87Pro, Asp90His, Asp90Tyr, etc.) (Wang et al, 1993;Bachoual et al, 2001;Piddock et al, 2003) mostly of in vitro origin (Bachoual et al, 2001). One isolate possessed another mutation in QRDR, Pro104Ser, previously described in isolates of animal and human origin (Piddock et al, 2003;Jesse et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Among the described mutations, Thr86Ile is the most prevalent (Bachoual et al, 2001), conferring high minimum inhibitory concentration (MIC) values. In addition to this mutation, several other point mutations at gyrA have been described at the same codon-Thr86Val (Piddock et al, 2003), Thr86Lys and Thr86Ala (Wang et al, 1993)-as well as in other codons: Ala87Pro, Asp90His, and Asp90Tyr. These other mutations confer resistance against quinolones with different MICs values.…”
Section: Introductionmentioning
confidence: 99%
“…In a study of quinolone-resistant Campylobacter a majority of isolates analysed were shown to possess a common mutation [128]. The predominant genetic alteration responsible for conferring resistance to ciprofloxacin in C. jejuni and C. coli is the result of a mutation in the gyrA gene, whereby many isolates tested demonstrated a Thr-86-Ile substitution in the A-subunit of DNA gyrase [185]. A Mismatch Amplification Mutation Assay (MAMA)-PCR has been successfully applied to the detection of ciprofloxacin resistance in C. jejuni and C. coli, and this protocol is a convenient screening tool among these isolates [196].…”
Section: Antimicrobial Susceptibility Testing In Campylobacter Sppmentioning
confidence: 99%
“…This observation may in turn, lead to Campylobacter-associated deaths among vulnerable members in the community. Resistance to fluoroquinolones arises following a point mutation [ACAATA], which produces a Thr-86-Ile amino acid substitution in the Quinolone Resistance Determining Region (QRDR) of the gyrA subunit-encoding gene [185]. Genetic alterations in this region are often associated with high-level resistance to nalidixic acid (MIC > 64-128 µg/mL) and ciprofloxacin (MIC > 16-64 µg/mL).…”
Section: Genetic Mechanisms Associatedmentioning
confidence: 99%
“…às fluoroquinolonas (Wang et al 1993, Wilson et al 2000, Bachoual eu al. 2001, Hakanen et al 2002, Qin et al 2011, Iovine 2013, Wieczorek & Osek 2013, Hungaro et al 2015.…”
Section: Discussionmentioning
confidence: 99%